2007
DOI: 10.1523/jneurosci.4391-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

EstradiolIn VivoRegulation of Brain Mitochondrial Proteome

Abstract: We used a combined proteomic and functional biochemical approach to determine the overall impact of 17␤-estradiol (E 2 ) on mitochondrial protein expression and function. To elucidate mitochondrial pathways activated by E 2 in brain, two-dimensional (2D) gel electrophoresis was conducted to screen the mitoproteome. Ovariectomized adult female rats were treated with a single injection of E 2 . After 24 h of E 2 exposure, mitochondria were purified from brain and 2D analysis and liquid chromatography-tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(192 citation statements)
references
References 46 publications
13
175
0
4
Order By: Relevance
“…1705226) revealed that there are at least two 86% homologous CREB sequences present in the genome (Sarkar et al, 2008, unpublished observation). Consistently, estrogens have been found to increase expression of mitochondrial coded cytochrome c oxidase subunits I, II, and II (Chen et al, 2004b;Chen et al, 2005;Hsieh et al, 2006;Nilsen et al, 2007;Yager and Chen, 2007).…”
Section: Erβ As a Mitochondrial Transcriptional Factormentioning
confidence: 86%
“…1705226) revealed that there are at least two 86% homologous CREB sequences present in the genome (Sarkar et al, 2008, unpublished observation). Consistently, estrogens have been found to increase expression of mitochondrial coded cytochrome c oxidase subunits I, II, and II (Chen et al, 2004b;Chen et al, 2005;Hsieh et al, 2006;Nilsen et al, 2007;Yager and Chen, 2007).…”
Section: Erβ As a Mitochondrial Transcriptional Factormentioning
confidence: 86%
“…Raben et al found that β-hydroxyacyl-CoA dehydrogenase (HADH) and CS levels were 20% lower in formerly obese women [46] . Moreover, pyruvate dehydrogenase, aconitase, and ATP-synthase are regulated by estrogen [47] . Therefore, more precursor acetyl-CoA may enter into the fatty acid, ketone (eg, acetoacetate, 3-hydroxy-butanoic acid, and acetone), and cholesterol biosynthesis processes as a result of the TCA cycle being attenuated under estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were determined using the BCA protein assay kit (Pierce). Western blot analysis was similar to a published procedure with minor modifications (36,37). Detailed methods are provided in the SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%